The Development of Conventional Constructivism and Critical Constructivism Approach in International Relations Theories - Setiyaningsih, Dewi (Universitas Sulawesi Barat, 2021)
This paper argues that Constructivism as the approach in International Relations are still debated. The debate is on Conventional (modern) and Critical (post-modern) constructivsm. Although both are claimed as critical approach (similar in their epistemological aspect) and emerged in the same context and same culture of school in IR, they are different in adopting the methodological aspect. It may caused by the constructivist itself grow along the growing of critical studies and the legacy of IR’s behavoralism which still remains dominantly. Thus, it makes one constructivist hold on to reflectivism too much and another constructivist engaged to positivism in order to prove that constructivism is scientific enough theoretically. Outlining the historical background both context and academic text, this paper analyze this issue in a path.